STUDI LITERATUR : HUBUNGAN POLA MENSTRUASI DAN TINGKAT KONSUMSI ZAT BESI DENGAN KEJADIAN ANEMIA PADA REMAJA PUTRI - Fendrawaty Fendra Hilamuhu (Program Studi Ilmu Kesehatan Masyarakat, Fakultas Kesehatan Masyarakat, Universitas Indonesia Timur, 2021)
ABSTRACT Anemia can cause fatigue, decreased learning concentration, decreased immune system therefore it is prone to infection.The objective of research was to determine the relationship between menstrual patterns and the level of iron consumption with anemia in adolescent girls.The design used is a descriptive narrative design with a literature review approach (literature study).Sources of data used are from research journals that have been previously researched, this research uses 6 journals.The result obtained there is relationship betweenmenstrual patterns and the level of iron consumption with anemia in adolescent girls because anemia influenced of (menstrual cycle, menstrual length and menstrual blood volume) and the level of iron consumption, besides anemia, is also caused by several other factors, namely direct factors and indirect factors. Direct factors, namely: the presence of infection caused by hookworms, malaria and tuberculosis, while the indirect factors that cause anemia are low socio-economic conditions, level of education and knowledge of nutrition. Conclusion: The conclusion of menstrual patterns, iron consumption affects anemia in adolescent girls. Keywords: Menstrual Pattern, Iron Consumption, Anemia, adolescents girl